2016
DOI: 10.1246/cl.160562
|View full text |Cite
|
Sign up to set email alerts
|

A Post-translational Cyclodehydratase, PatD, Tolerates Sequence Variation in the C-terminal Region of Substrate Peptides

Abstract: A mutagenesis study of the downstream recognition sequence (dRS) in the substrate peptide of a post-translational cyclodehydratase, PatD, was conducted by means of an in vitro reconstituted translation system integrated with PatD, named the FIT-PatD system. The results have revealed that PatD tolerates various dRS sequences, enabling the one-pot biosynthesis of azoline-containing peptides (Az-peptides) with various Cterminal tag sequences such as hexahistidine, FLAG epitope, and Avi-tag.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…In this system, referred to as the FIT‐PatD system, precursor peptides are expressed from synthetic DNA templates, and the Cys/Ser/Thr residues in the CP region are subsequently cyclodehydrated by PatD in a one‐pot manner; this allows high‐throughput analysis of the substrate tolerance of PatD. Previous mutagenesis studies of the precursor peptides with the FIT‐PatD system have demonstrated the remarkable ability of PatD to process various artificial precursor peptides with Cys/Ser/Thr residues . The major advantage of the FIT system is that it can facilitate reprogramming of the genetic code to express peptides containing diverse non‐proteinogenic amino acids.…”
Section: Figurementioning
confidence: 99%
“…In this system, referred to as the FIT‐PatD system, precursor peptides are expressed from synthetic DNA templates, and the Cys/Ser/Thr residues in the CP region are subsequently cyclodehydrated by PatD in a one‐pot manner; this allows high‐throughput analysis of the substrate tolerance of PatD. Previous mutagenesis studies of the precursor peptides with the FIT‐PatD system have demonstrated the remarkable ability of PatD to process various artificial precursor peptides with Cys/Ser/Thr residues . The major advantage of the FIT system is that it can facilitate reprogramming of the genetic code to express peptides containing diverse non‐proteinogenic amino acids.…”
Section: Figurementioning
confidence: 99%
“…For the first step, we have previously developed an in vitro biosynthetic system of thiazoline‐containing peptides by integrating a custom‐made cell‐free translation (flexible in‐vitro translation; FIT) system with the cyclodehydratase PatD . In this system, referred to as the FIT‐PatD system, precursor peptides composed of an N‐terminal leader peptide (LP) region followed by a core peptide (CP) region containing Cys residues are ribosomally synthesized from synthetic DNA templates, and then the Cys residues in the CP are posttranslationally modified by PatD to thiazolines with tolerance for a broad substrate sequence, allowing one‐pot production of diverse thiazoline‐containing peptides . We envisioned that the thiazolines could be converted into thiazolidine using a mild reducing agent that tolerates aqueous conditions (2nd step).…”
Section: Figurementioning
confidence: 99%
“…Goto et al, 2014). Although PatD tolerates noncanonical C-terminus RSIII, it still influenced the catalytic efficiency to some extent (Yuki Goto & Suga, 2016). …”
Section: Heterocyclasementioning
confidence: 99%